Confronting Race Head-on in 12 Years a Slave (Steve McQueen, 2013): Redefining the Contours of the Classic Biopic? - Anne-Marie Paquet-Deyris (Transatlantica)
In his successful 2013 cinematic release 12 Years a Slave, Steve McQueen circumvents the “great white narrative” by addressing race “head-on” instead of metaphorically, writing every character within their own racial background. As in Solomon Northup’s 1853 Twelve Years a Slave, black characters are not removed from their own histories; instead, they are shaped and defined by them. To what extent, then, does the film distinctly voice racial concerns and tensions, and provide representational spaces on screen in a nuanced and reflective manner? How does it—if indeed it does—subvert the standard black slave/character and white master/hero dynamic, and embrace a wide variety of black stories and perspectives? By reconsidering the classic biopic/historical film, this article examines how the movie relocates America’s problems with race at the very heart of the national debate and offers a “post-post-racial” screen model that directly confronts race history.